PENGARUH GOOD CORPORATE GOVENANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAN SUB SEKTOR BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulyaningtyas Mulyaningtyas; Foni Dian Candra (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2021)
This study aims to determine the effect of independent commissioners, boards of directors, audit committees, and company size on ROA in banking companies listed on the IDX, using the classical assumption test, multiple linear regression, coefficient of determination (R2) test, and hypothesis testing. The sample used in this study is a banking company listed on the Stock Exchange for the period of 2016-2018 using a puposive sampling method. Data sources used in this study are secondary data obtained from annual financial reports that have been audited sourced from www.idx.co.id. With data analysis techniques using multiple linear regression analysis. The results showed that the independent board of commissioners and audit committee had no effect on ROA in banking companies, while the board of directors and company size affected ROA in banking companies listed on the IDX